People of the screen how evangelicals created the digital Bible and how it shapes their reading of scripture - Dyer, John 1972- (New York Oxford University Press, 2023)
"This book traces the history of Bible software and app development, showing the unique and powerful role evangelical entrepreneurs and coders have played in shaping its functionality and how their choices in turn shape the reading habits of millions of people around the world. Though evangelicals are sometimes seen as those who retreat from or reject societal change, this book argues that evangelicals are adept at appropriating new technology-including early computers, the internet, mobile apps, and virtual reality experiences-in service of what they see as their mission in the world. In addition to historical research, this book includes interviews with developers at three of the largest Bible software companies and field work with digital and print Bible readers in several church. This creates a comprehensive look at the interconnected ecosystem of publishers, developers, pastors, institutions, and software companies both within and outside of evangelicalism, and demonstrates how it affects the way churchgoers read and interpret the Bible"--
Includes bibliographical references and index
Keywords: Bible -- Criticism, interpretation, etc -- Data processing; Bible -- Reading; Bible and technology; Evangelicalism